Circulation of pertussis and poor protection against diphtheria among middle-aged adults in 18 European countries - Berbers Guy; van Gageldonk Pieter; van de Kassteele Jan; Wiedermann Ursula; Desombere Isabelle; Dalby Tine; Toubiana Julie; Tsiodras Sotirios; Ferencz Ildikó Paluska; Mullan Kathryn; Griskevicius Algirdas; Kolupajeva Tatjana; et al. (Nature Research, 2022)
Reported incidence of pertussis in the European Union (EU) and the European Economic Area (EEA) varies and may not reflect the real situation, while vaccine-induced protection against diphtheria and tetanus seems sufficient. We aimed to determine the seroprevalence of DTP antibodies in EU/EEA countries within the age groups of 40-49 and 50-59 years. Eighteen countries collected around 500 samples between 2015 and 2018 (N = 10,302) which were analysed for IgG-DTP specific antibodies. The proportion of sera with pertussis toxin antibody levels ≥100 IU/mL, indicative of recent exposure to pertussis was comparable for 13/18 countries, ranging between 2.7-5.8%. For diphtheria the proportion of sera lacking the protective level (<0.1 IU/mL) varied between 22.8-82.0%. For tetanus the protection was sufficient. Here, we report that the seroprevalence of pertussis in these age groups indicates circulation of B. pertussis across EU/EEA while the lack of vaccine-induced seroprotection against diphtheria is of concern and deserves further attention.